A rare co-existence of langerhans cell histiocytosis and lichen planus - Aarti S Salunke; Anil P Gosavi; Ravindranath B Chavan; Pallavi Prataprao Patil (Wolters Kluwer Medknow Publications, 2018)
Langerhans cell histiocytosis (LCH) is the commonest of the histiocytic disorders. Owing to the relative rarity of the condition, it remains a disease in which the diagnosis is often delayed or missed. Commonly seen in infancy or early childhood, the disorder is characterized by proliferation of abnormal and clonal Langerhans cells in skin, bone, lymph nodes, lungs, liver, spleen, and bone marrow. Lichen planus presents as purple, polygonal, pruritic, papular eruption of unknown etiology affecting skin, mucous membranes and nails. Despite of thourough literature search, we could not find any association of lichen planus with LCH. Hereby, we report a case of five year old child with acute onset of polymorphic eruptions all over the body which on histopathology and Immunohistochemistry showed features of Langerhans cell histiocytosis and lichen planus on bilateral lower limb.